A structural and functional study of the retina in patients with schizophrenia (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To examine the relationship between retinal structural parameters and visual perception function in patients with schizophrenia.Material and Methods: Twenty-four subjects (48 eyes) were included in the study. Group 1 (the schizophrenia group) comprised 11 patients with paranoid schizophrenia and one with schizotypical personality disorder, and Group 2 (the control group) comprised 12 mentally healthy subjects. Group 1 was subdivided into Subgroup A (disease duration of > 5 years) Subgroup B (disease duration of < 5 years). Subjects underwent a routine eye examination, assessment of contrast sensitivity threshold using Ergotest 3.0 software, and optical coherence tomography (OCT) of the retina using a Topcon 3D OCT 2000 apparatus in 3D Macula, Radial Macula and 3D Disc modes.Results: Compared to the control group, the patients with schizophrenia exhibited significantly (p < 0.05) lower contrast sensitivity threshold values at high spatial frequencies. The contrast sensitivity threshold at high spatial frequencies was negatively correlated with disease duration (p=0.046, r=-0.585). OCT-based macular parameters and the diameter of the foveola in these patients tended to increase compared with controls, but only differences in the macular volume (p = 0.035), superior inner retinal thickness (p = 0.022) and nasal inner retinal thickness (p = 0.003) for both eyes were significant.Conclusion: Our findings in patients with schizophrenia confirm previously reported evidence of dysfunction of the parvocellular visual channels in the early disease stages. In addition, they confirm the hypothesis that there is an association of an acute psychotic episode with neuroinflammation and subclinical retinal edema in the macula.
Keywords: schizophrenia; optical coherence tomography; macular volume; retinal contrast sensitivity